A study of dielectrophoretically aligned gallium nitride nanowires in metal electrodes and their electrical properties - Lee, S. -Y.; Kim, T. -H.; Suh, D. -I.; Cho, N. -K.; Seong, H. -K.; Jung, S. -W.; Choi, H. -J.; Lee, S. -K. (ELSEVIER, 2006)
We quantitatively characterized the ac dielectrophoresis force on semiconducting gallium nitride (GaN) nanowires in suspension with variations of the ac electric field and frequency. The yield of aligned GaN nanowires increased with increasing ac electric field (up to 20 Vp-p). The yield results indicate that the GaN nanowires were well aligned with a high yield of similar to 80% over the entire array in a chip at the frequencies of 10 kHz and 20 MHz. In addition, the electrical properties of GaN nanowires prepared by dielectrophoresis were investigated using conventional three-probe schemes in field-effect transistor structures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: MANIPULATION; FABRICATION